THE RESISTANCE AND ACCEPTANCE OF THE MAJELIS TAFSIR ALQURAN’S ISLAMIC PREACHING METHODS - Muhammad Farkhan Mujahidin; Istadiyantha Istadiyantha; Abdullah Wakit; Ediyono Suryo (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
When da'wah is practiced by an individual or a group of community members, the consequence is always acceptance or rejection. The problem of da'wah of the Majelis Tafsir Alquran (MTA) Surakarta and its branches and representatives in Indonesia is criticism, blasphemy, rejection, and acceptance of these activities and movements. The most serious resistance emerges from groups upholding regional religious and cultural traditions, despite this strong opposition, MTA also grows widespread in areas where people find a match for their fresh perspectives. The objective of this study is to determine how a da'wah institution can develop and establish several branches and representatives in a short period of time yet remain accepted by the community. In this study, primary and secondary data sources were interviews and direct field observation. To obtain a balanced view of the interpretation over MTA's religious social movement acceptance and resistance, the descriptive qualitative analysis research typology was used. The findings revealed that several factors, including leadership, da'wah attitudes and methods, the competence and abilities of da'wah actors, and acceptance and ideological differences among da'wah targets, contribute to MTA's resistance and acceptance of its da'wah.